Measurement of composition of organic constituents of municipal wastewater for plant-wide modelling - Brink, I (Department of Civil Engineering, 2023)
Historically wastewater treatment unit operation models have been developed in isolation. Attempts have been made at creating common platform models, which would allow modellers to speak a common language when researching wastewater treatment modelling. However, few attempts have been made at integrating different models into a plant-wide WWTP simulation model. Increasing pressure towards the optimisation of water treatment systems have prompted investigation into integrated WWTP modelling. The use of different state variables in WWTP unit operation models has meant that modelling incompatibilities exist in the theoretical coupling of certain models. Attempts made towards the development of integrated WWTP models have experienced difficulties due to a number of factors. State variables required in one model may be non-existent in other models, the definition of state variables may be different between different unit process models and compounds that are considered constant in a unit process model may be a state-variable in another unit process model Thus the difficulties in coupling different unit process models are mainly due to differences in state variable meaning and occurrence in different unit process models. Recent approaches towards the development of plant-wide WWTP simulation models have included the continuity based interfacing method (CBIM) of Vanrolleghem et al. (2005) and Volcke et al. (2006), the 'supermodel approach' of Jones &Tákacs (2004 cited in Grau et al 2007) and Seco et al. (2004 cited in Grau et al 2007) , the transformation based approach of Grau et al. (2007) and the mass balances based plant-wide WWTP model approach of Ekama et al. (2006 a,b), Sötemann et al. (2006) and Wentzel et al. (2006). The use of compounds in their elemental composition forms, viz. C, H, O, N, P and charge content, as part of a method to transform incompatible unit process state variables into compatible forms is a general theme in integrated modelling approaches. The elemental compositions of readily biodegradable (RB), slowly biodegradable (SB), unbiodegradable soluble (US) and unbiodegradable particulate (UP) organic compounds are often unknown. Little practical investigation into their determination for the purpose of integrated WWTP modelling has been performed. This project was therefore focussed on the determination of wastewater compound elemental compositions, with the inclusion of carbon data, for integrated WWTP modelling purposes. The aims of this project were therefore two fold, viz. an investigation into current whole WWTP integration model approaches and the performance evaluation of a simple batch test method for the determination of organic compound elemental compositions over a standard WWTP incorporating primary settling, an AS reactor as well as primary sludge and WAS anaerobic digestion. A simple anaerobic batch test approach towards determining wastewater organics total, biodegradable and unbiodegradable as well as soluble and particulate fraction elemental compound compositions was investigated. This approach was evaluated according to the fulfilment of three research objectives, viz. (1) the fractionation of raw wastewater, PS and WAS organics into biodegradable and unbiodegradable soluble and particulate components, (2) the fractionation of raw wastewater concentrations (C,N,COD,VS) into settlable and colloidal particulate organic material, (3) the determination of the organic compositions of the form CxHyOzNa for the above wastewater and sludge fractions. Research performed by Wentzel et al. (2006) and Ekama et al (2006 b) have supported the notion that organic material termed unbiodegradable from an activated sludge standpoint remain unbiodegradable under anaerobic digestion processes. Thus, the use of an anaerobic batch test method for determination of unbiodegradable organic compositions over a plant-wide WWTP was considered to be valid. The first experimental research objective, viz. the fractionation of raw wastewater, PS and WAS into unbiodegradable and biodegradable fractions was considered to have been achieved. However, the accuracies of these fractionations were found to be inadequate to determine colloidal and settlable raw wastewater unbiodegradable and biodegradable fractions. Four different calculation methods with different requisite data sets were used to calculate particulate organic compound elemental compositions. The results were variable and this was ascribed to data inaccuracy. The calculation methods used for the determination of organics compositions was found to be highly sensitive to input variable error. This indicated that the indirect determination of particulate organics compositions requires measured data of very high accuracy. It was considered doubtful whether such accuracies may be achieved with the batch test method evaluated in this chapter. Therefore the second and third experimental research objectives, viz. the fractionation of raw wastewater concentrations into settlable and colloidal particulate organic material and the determination of unbiodegradable and biodegradable organics compositions for different wastewater streams could not be ascertained with the batch test method used. Therefore, the batch test method designed and evaluated in this project was considered to be invalid for the determination of readily biodegradable, slowly biodegradable, unbiodegradable soluble and unbiodegradable particulate organic compound elemental compositions at links between unit operations over a WWTP.